The Role Of Human Resources In Lake Transportation To Improve Tourism Service In Lake Toba - Jhonson Pardosi; Robert Sibarani; Nur Cahaya Bangun (Program Studi Pengembangan Masyarakat Islam, 2021)
The objective of this research is to: discover the role of Human Resources to support the Tourism Transportation Service Standard in Samosir Regency. The type of the research is a qualitative research with descriptive method. The object of this research is human resources in transportation sector, there are regulator, transportation service provider, and ship crews. All of them are local communities around lake Toba. The data are collected by employing 3 methods; they are observation, interview, and documentation. The results of the research are that Regulator plays the roles as policy maker, stimulator, and facilitator; Crossing Transportation Service Provider plays the roles as policy implementor, organizer, and operator; and Ship Crews play the roles as the policy implementor and executor.